2011
DOI: 10.1016/j.mrgentox.2010.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenicity and genotoxicity of isatin in mammalian cells in vivo

Abstract: Isatin (1H-indole-2,3-dione) is a synthetically versatile substrate used for the synthesis of heterocyclic compounds and as a raw material for drug synthesis. Isatin and its derivatives demonstrate anticonvulsant, antibacterial, antifungal, antiviral, and anticancer properties. We evaluated the genotoxic and mutagenic effects of acute (24h) and repeated (14d) exposure to isatin in vivo, using the comet assay and the micronucleus test. Three doses (50, 100, and 150mg/kgb.w.) were administered to mice via gavage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 43 publications
2
10
0
Order By: Relevance
“…Studies by Jongen and Alink (1982) support the present results, they examined the mutagenic potential of two natural and seven synthetic commercial indigo products and they reported that natural products showed no mutagenicity in Salmonella typhimurium strains TA98 and TA100 but all of the synthetic products were found mutagenic. Also our results coincided with previous studies by Candido-Bacani et al (2011) which evaluated genotoxic and mutagenic effects of acute (24 h) and repeated (14 day) exposure to isatin as indigo precursor in vivo, and the results showed that the mutagenic and genotoxic effects of isatin depended on dose and-exposure period.…”
Section: Sister-chromatid Exchange (Sce) and Mitotic Indices (Mi) Ressupporting
confidence: 91%
See 3 more Smart Citations
“…Studies by Jongen and Alink (1982) support the present results, they examined the mutagenic potential of two natural and seven synthetic commercial indigo products and they reported that natural products showed no mutagenicity in Salmonella typhimurium strains TA98 and TA100 but all of the synthetic products were found mutagenic. Also our results coincided with previous studies by Candido-Bacani et al (2011) which evaluated genotoxic and mutagenic effects of acute (24 h) and repeated (14 day) exposure to isatin as indigo precursor in vivo, and the results showed that the mutagenic and genotoxic effects of isatin depended on dose and-exposure period.…”
Section: Sister-chromatid Exchange (Sce) and Mitotic Indices (Mi) Ressupporting
confidence: 91%
“…Natural Isatis plants, some indigo precursors and indirubin were also tested for their genotoxicity (Candido-Bacani et al 2011) and indirubin and its derivatives were found to possess low toxicity (Zhen et al 2007). In natural Isatis plants, some indigo precursors and indirubin known as red isomer of indigo were also tested for their genotoxicity (Candido-Bacani et al 2011) and indirubin and its derivatives were reported to possess low toxicity (Zhen et al 2007).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Isatin was first synthesized by Erdmann and Laurent in 1840 [2]. Isatin and triazole containing heterocyclic compounds are reported as a cure of lethal diseases [3].…”
Section: Introductionmentioning
confidence: 99%